Regulation of astrocyte pathology by fluoxetine prevents the deterioration of Alzheimer phenotypes in an APP/PS1 mouse model. Issue 2 (8th October 2015) - Qiao, Jinping; Wang, Junhui; Wang, Hongxing; Zhang, Yanbo; Zhu, Shenghua; Adilijiang, Abulimiti; Guo, Huining; Zhang, Ruiguo; Guo, Wei; Luo, Gang; Qiu, Yiqing; Xu, Haiyun; et al.
Abstract : Studies have implicated astrocytic dysfunction in Alzheimer's disease (AD). However, the role of astrocytes in the pathophysiology and treatment of the disease is poorly characterized. Here, we identified astrocytes as independent key factors involved in several Alzheimer‐like phenotypes in an APP/PS1 mouse model, including amyloid pathology, altered neuronal and synaptic properties, and impaired cognition. In vitro astrocytes from APP/PS1 mice induced synaptotoxicity as well as reduced dendritic complexity and axonal branching of hippocampal neurons. These astrocytes produced high levels of soluble β‐amyloid (Aβ) which could be significantly inhibited by fluoxetine (FLX) via activating serotonin 5‐HT2 receptors. FLX could also protect hippocampal neurons against astrocyte‐induced neuronal damage in vitro . In the same APP/PS1 mice, FLX inhibited activation of astrocytes, lowered Aβ products, ameliorated neurotoxicity, and improved behavioral performance. These findings may provide a basis for the clinical application of FLX in patients, and may also lay the groundwork for exploration of other novel astrocyte‐based therapies of AD. GLIA 2016;64:240–254 Main points: Astrocytes are responsible for several phenotypes in AD mouse, including amyloid pathology, altered synaptic properties and impaired memory. Astrocytes from AD mice caused synaptotoxicity and neurotoxicity of hippocampal neurons in cultures, which can be attenuated by the treatment of fluoxetine.